(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Gestational diabetes mellitus (GDM) is a prevalent pregnancy-related metabolic disorder that contributes to significant maternal and neonatal complications. The role of vitamin D in improving glycemic regulation has been well researched, but appropriate dosing strategy remains uncertain. Objective: To compare the effects of low-dose versus high-dose vitamin D supplementation on fasting blood sugar (FBS) and insulin resistance (HOMA-IR) in pregnant women diagnosed with GDM. Methods: This randomized controlled trial was carried out at Sir Ganga Ram Hospital, Lahore, from 1st January 2025 to 31st May 2025. A total of 300 pregnant women with GDM (gestational age 24–37 weeks) were randomized into two groups. Group A was given vitamin D (2,500 IU every two weeks), whereas Group B received vitamin D (50,000 IU every two weeks). FBS and HOMA-IR were measured at baseline, after 15 days, and at one month. Data analysis was performed using SPSS v25. Results: After one month of supplementation, the mean FBS levels dropped to 112.6 ± 10.4 mg/dl in the Group A and to 98.8 ± 9.8 mg/dl in the Group B (p < 0.001). Similarly, mean HOMA-IR decreased to 3.88 ± 0.9 in Group A and 2.95 ± 0.8 in Group B (p < 0.001). Conclusion: High-dose vitamin D supplementation was more effective than low-dose therapy in improving glycemic parameters among women with GDM. Hence, higher vitamin D regimens may be beneficial as adjunctive therapy to optimize metabolic control in this population.